2020
DOI: 10.7150/ijms.33992
|View full text |Cite
|
Sign up to set email alerts
|

FAM83A is amplified and promotes tumorigenicity in non-small cell lung cancer via ERK and PI3K/Akt/mTOR pathways

Abstract: Family with sequence similarity 83A (FAM83A) is a newly-found over-expressed oncogene in several types of cancers and associates with poor prognosis. However, the role that FAM83A may play in the carcinogenesis of non-small cell lung cancer (NSCLC) still needs to be defined. The present study aimed to investigate the function of FAM83A in NSCLC progression and to investigate the possible mechanism. Analysis of Gene Expression Omnibus (GEO) database and rt-PCR showed up-regulated expression of FAM83A in NSCLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…This signaling pathway is mediated through serine and/or threonine phosphorylation of different types of downstream compounds, of them PI3K and AKT are the main proteins. The effects of FAM83A on PI3K/AKT pathway have been investigated in few cancers (22,(35)(36)(37). Liu et al analyzed TCGA database and reported that FAM83A is overexpressed in hepatocellular carcinoma (HCC) cells and plays a cancer-promoting and treatmentresistance role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This signaling pathway is mediated through serine and/or threonine phosphorylation of different types of downstream compounds, of them PI3K and AKT are the main proteins. The effects of FAM83A on PI3K/AKT pathway have been investigated in few cancers (22,(35)(36)(37). Liu et al analyzed TCGA database and reported that FAM83A is overexpressed in hepatocellular carcinoma (HCC) cells and plays a cancer-promoting and treatmentresistance role.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al examined the roles and possible mechanism of FAM83A in non-small cell lung cancer (NSCLC) progression through bioinformatics analysis of GEO and TCGA databases and RT-PCR and reported high FAM83A expression in NSCLC that was associated with the poor prognosis (35). In vitro model showed that silencing FAM83A by siRNA/shRNA markedly reduced cell proliferation, induced cell apoptosis, and inhibited cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that AKR1B10 can promote proliferation and migration/invasion of breast cancer cells via the ERK and FAK/Src/Rac1 signaling pathway [8,32]. Several studies have also demonstrated that PI3K/AKT and MEK/ERK signaling pathways can be activated in tumors together [33][34][35]. AKR1B10 may affect several signaling pathways in BC.…”
Section: Discussionmentioning
confidence: 99%
“…promotes lung cancer progression by regulating the Wnt and Hippo signaling pathways. Hu HY et al found that FAM83A promotes tumorigenesis of NSCLC at least partly via ERK and PI3K/Akt/mTOR pathways, making it a promising therapeutic target (13) . Zhou FR et al (19) found that co-expression of FAM83A and PD-L1 in tumor cells was a credible biomarker predictor for worse survival in resected LAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing studies have found that dysregulated FAM83A is a potential biomarker in various cancers, including breast, hepatocellular and lung adenocarcinoma cancers (7; 8; 9; 10; 11; 12) . It was reported that FAM83A promotes lung adenocarcinoma cancer progression by regulating the Wnt and Hippo (8) and ERK and PI3K/Akt/mTOR pathways (13) , making it a promising therapeutic target. Besides, circ-ZKSCAN1/miR-330-5p/FAM83A feedback loop plays important role in promoting the progress of NSCLC (14) .…”
Section: Introductionmentioning
confidence: 99%